Peningkatan Akurasi dan Kecepatan Pelacakan Bola Sepak Dengan Menggunakan Metode Camshift - Muhammad Luqman Bukhori (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2020)
The robot is an automatic control tool to help human work. Types of robots that can be applied such as in military, health, and the like. One type that can be applied is a robot to track an object. Object tracking requires unique and varied characteristics and characteristics. For example object color, shape texture, and size. With these many features and characteristics, robots are required to be able to identify and track an object quickly and accurately just like humans. Based on the problems experienced, there is one solution to solve tracking quickly and accurately, namely by implementing the CAMSHIFT algorithm or method. This method can overcome several features and characteristics of an image in a varied way because of its adaptability to its environment. In this research, this method is applied to track an object, namely a soccer ball. This soccer ball has a characteristic orange color, with several patterns surrounding it. The results obtained after applying this method, the robot can perform fast-tracking of spherical objects up to 0.0857 seconds per frame. Further testing was carried out by setting the ball reach distance to 10 meters. The results of this distance test show that the robot can track the ball over the entire distance with 100% accuracy.